Viability of bhk-21 fibroblast cells toward acrylic denture bases after reinforced by natural fibers - Prawesthi, Endang; Tetelepta, Marzia Magdalena; Heldayani, Heldayani; Kastian, Ria Fajarwati; Septisetyani, Endah Puji (Jurnal Teknosains, 2024)
The use of acrylic denture bases in the oral cavity requires biocompatibility. This study investigated the viability of BHK-21 fibroblast cells after treatment with an acrylic denture base modified using natural fibers. Ramie and banana stem fibers were used as cost-effective alternatives to synthetic fibers. The study involved 42 acrylic resin specimens (10 mm diameter, 2 mm thickness) divided into groups: resin without fibers, 0.5%, 1.5%, and 2.5% ramie fibers, and 0.5%, 1.5%, and 2.5% banana stem fibers. The resin was incubated with cell culture media at 37°C for 7 days. Cytotoxicity testing using the MTT method revealed that all treatment groups had cell viability exceeding 70%, meeting ISO 10993-5 standards. No significant differences in cell viability were observed between the treatment groups and the control (media without specimens). Additionally, adding 0.5%, 1.5%, and 2.5% ramie fibers did not affect BHK-21 cell viability compared to the resin-only control, while adding banana stem fibers increased cell viability compared to the control (P = 0.035; P = 0.021; and P = 0.011). In conclusion, increasing the concentration of natural fibers in acrylic denture bases did not negatively impact fibroblast cell growth.